Prevalence and antibiogram of Pseudomonas aeruginosa and Staphylococcus aureus clinical isolates from burns and wounds in Duhok City, Iraq - Ali, Samir; Assafi, Mahde (The Journal of Infection in Developing Countries, 2024)
Introduction: this study aimed to isolate P. aeruginosa and S. aureus, investigate the antimicrobial resistance of collected isolates, and investigate the distribution of exoU and mecA genes in P. aeruginosa and S. aureus isolates. Methodology: Out of 150 samples, 32 isolates were identified as P. aeruginosa, 48 isolates were identified as S. aureus. All isolates were checked for AST. Then, a PCR was applied to detect exoU and mecA genes in P. aeruginosa and S. aureus. Results: 12.0% and 29.3% of the samples showed co-isolates and single isolates of studied pathogens, respectively. Regarding burn samples, S. aureus was the most prevalent pathogen (38.0%, 38/100) among males (41.8%, 23/55), followed by P. aeruginosa (27.0%, 27/100) among females (28.9%, 13/45). The highest burn infection rates of S. aureus (50.0%) and P. aeruginosa (32.7%) were recorded among age groups (≥ 50) and (18-49), respectively. Comparatively, wound samples were less infected with these pathogens. P. aeruginosa isolates usually exhibited high resistance to gentamicin, tobramycin, and netilmicin, whereas, imipenem showed low resistance at 46.87%. S. aureus isolates were susceptible to trimethoprim-sulphamethoxazole and rifampin. 56.25% of P. aeruginosa isolates were exoU positive and 37.5% of S. aureus isolates were mecA positive. Results of the cefoxitin inhibition zone with mecA gene amplification, 33.3% isolates were MRSA, 4.2% isolates were nmrMRSA, and 62.5% isolates were MSSA. Most of the resistant isolates of P. aeruginosa carried the exoU gene, 80% resistant isolates to imipenem were exoU positive. Conclusions: S. aureus was more predominant than P. aeruginosa in burns and wounds infections.